Evaluation of Antibiotic Utilization in Otitis Media and Otitis Externa in Tertiary Care Hospital - Zulekha, Suha; Devadiga, Sumithra; Shyma, Zuha; P, Sajan Francis; S, Mangala; Veigas, Grinton Josvi; R, Ravikumar (Indian Journal of Pharmacy Practice)
Background: This present study aimed to determine the current prescribing pattern for otitis media and otitis externa in a tertiary care hospital. Materials and Methods: This cross-sectional study involved 120 patients clinically diagnosed with active otitis media and otitis externa. The data source was collected from case reports, treatment charts, and suitably designed documentation forms. Results: A total of 296 antibiotics were prescribed, and with respect to class of antibiotics, fluoroquinolones (37.8%) were the most commonly prescribed, followed by aminoglycosides (25.33%). 164 empirical antibiotics were prescribed to 97 patients. There were 132 definitive antibiotics prescribed, with neomycin accounting for 11.82 percent of them. The antibiotics were prescribed as dual therapy in 52 patients (43.33%), followed by triple therapy in 48 patients (40%), and monotherapy in 19 patients (15.83%), whereas one patient was not prescribed any antibiotics. Conclusion: The most commonly prescribed antibiotics in our study were fluoroquinolones. The analysis of prescription patterns is essential to improving the utilisation of drugs and should be carried out frequently. The study result aims at focusing attention on the importance of strategies that have to be carried out to rationalise the use of medications in patients with otitis media and otitis externa.
Keywords: Antibiotic utilization; Antibiotics; Otitis media; Otitis externa; Prescribing pattern